Syllabus cours gestion des risques climatiques licence 3 - Sow, Sadibou (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This course aims to equip students to understand and manage the risks associated with climate change, particularly in the Senegalese agricultural context. It covers basic climate concepts, forecasting, decision-making under uncertainty and adaptation strategies. Specific themes include climate communication, gender and livestock farming in the face of climate change. The course adopts an active teaching approach (case studies, simulations, group work) and is assessed by an examination (60%) and a case study (40%). It is part of the ‘Value Chain and Risks’ unit, with a timetable of 15 hours. This module is essential for mastering current climate issues and providing effective support to producers in the face of hazards.